Penerapan LKPD Berbasis Inquiry Lesson untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik pada Materi Sistem Pencernaan Manusia - Rina Oktaviana; Eni Nuraeni; Amprasto Amprasto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study aims to analyze the increase in scientific literacy skills through the implementation of Inquiry Lesson-based worksheets on the material of the human digestive system. The research method used was quasi-experimental with a non-randomized control group pre-test and post-test research design. Participants were taken from two classes from class XI MIPA, with the cluster random sampling technique two classes XI MIPA were randomly selected with specifications for experimental class 1 and experimental class 2, each consisting of 32 students. The data were obtained using the instrument of scientific literacy questions in the PISA framework, totaling 10 in the form of valid and reliable multiple choice questions. The results showed that there was a significant difference as evidenced by the results of hypothesis testing with Sig. (2 tailed) = 0.000 <0.05, then ???????? is rejected and ???????? is accepted. There is a difference in the t-count of the experimental class 1 and the t-count of the experimental class 2 where the t-count of the experimental class 2 is 53.82 > 21.997, so it can be concluded that the scientific literacy skills of the experimental class using inquiry-based LKPD have increased scientific literacy skills higher.